1997
DOI: 10.1007/pl00006969
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous Jasmonic and Abscisic Acids Act Differentially in Elongating Tissues from Oat Stem Segments

Abstract: Segments can be cut from the peducular-1 internode of oat (Avena sativa L.) shoots so as to contain the graviresponsive, auxin-sensitive leaf sheath pulvinus, and the gibberellin-sensitive internodal tissue. These two growth-capable tissues were used to study the effects and interactions of jasmonic acid (JA) and abscisic acid (ABA) in regulating cell elongation. When supplied alone at physiologic concentrations (10 −5 , 10 −4 M), JA promoted growth and cell wall synthesis in the internodal tissue, whereas by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
9
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 30 publications
(53 reference statements)
1
9
0
Order By: Relevance
“…However, more recent work suggests that JA alone does not inhibit growth (Montague 1997, Ueda et al 1994Ueda et al , 1995 and may in some instances even promote growth as in oat internode tissue (Montague 1997). Our results indicate that JA at physiological concentrations of 10 −9 -10 −5 M can inhibit elongation growth in etiolated maize coleoptiles (Fig.…”
Section: Discussionsupporting
confidence: 53%
See 4 more Smart Citations
“…However, more recent work suggests that JA alone does not inhibit growth (Montague 1997, Ueda et al 1994Ueda et al , 1995 and may in some instances even promote growth as in oat internode tissue (Montague 1997). Our results indicate that JA at physiological concentrations of 10 −9 -10 −5 M can inhibit elongation growth in etiolated maize coleoptiles (Fig.…”
Section: Discussionsupporting
confidence: 53%
“…that JA antagonizes elongation-promoting signals such as IAA and GA. For example, elongation growth promoted by auxin in oat coleoptiles and pulvini was inhibited by JA (Montague 1997, Ueda et al 1994, 1995 as was GA-promoted elongation in oat internodes (Montague 1997). In this work, we have found that JA or JA-Me at concentrations from 10 −8 , 10 −7 , and 10 −5 M inhibited the IAA-induced growth of excised maize coleoptiles (Figs.…”
Section: Discussionmentioning
confidence: 47%
See 3 more Smart Citations